Evaluation of maxillary anterior endodontically treated teeth restored with different types of crowns - Al Moaleem, Mohammed; A Mobaraky, Abdulrahman; A Madkhali, Hassan; R Gohal, Muneera; M Mobaraki, Amna; H Adawi, Ebithag; M Kariri, Fahad; H Judayba, Musab; M Qohal, Mosaab; Alghazali, Nabiel (International Journal of Dental Research, 2017)
Statement of the problem: restoring endodontically treated teeth (ETT) is one of the major treatments provided by a dentist. Glass fiber posts (GFP) showed good clinical performance during last few years.Aim of the study; to assess and compare the clinical as well as the radiographic performance of different types of ceramic crown systems used in restoration of maxillary anterior teeth over a cemented GFP and composite resin core.Materials and methods: 50 ETT with GFP were included in this study. These teeth were divided into four gropes (composite resin. Porcelain fused to metal (PFM), e. max and zirconia restorations). Both the clinical and radiographic assessments were done for the restoration at a period of one week, 3, 6, 9, and 12 months after composite build up and crown's cementations. All data were registered and analyzed by SPSS program using percentages and Kaplan-Meyer analysis. Fisher’s exact test was used for categorical values while log-rank test was used for descriptive statistical analysis.Results: the clinical assessment showed no changes in the one week, 3 and 6 months in the four groups. While during the 9 and 12 months, a movement of the crown margin under finger pressure was present in one case, loss or retention in 2 cases of zirconia, the periodontal status with violation of biological width was present in one case of PFM and finally the color changes were obvious in one case of PFM and 2 cases of composite restoration. All the restorations in the four groups had no radiographic changes in the one week and three-month assessments. While during six-month follow-up, a loosed of retention in one case of the zirconia crown was detected. At the 9 and 12 months, two cases showed recurrent caries at the cervical margin of the composite restoration, cases with periapical infection and other with loss of retention of the post were recorded in the PFM restoration.Conclusion: e. Max and zirconia all ceramic crowns showed better clinical and radiographic performance than the PFM and composite restorations over 12 months recall.